Serotonin and norepinephrine reuptake inhibitor antidepressants: a look through the prism of their 30-year history - D. S. Danilov (Неврология, нейропсихиатрия, психосоматика, 2018)
Based on the data available in the literature, the author has first systematized in detail the main stages of the design and clinical introduction of serotonin and norepinephrine reuptake inhibitor (SNRI) antidepressants. Theoretical prerequisites for their emergence are described. The evaluation of the efficiency of depression therapy with drugs of this group in clinical trials and post-marketing studies is analyzed in the historical context. The reasons for temporary restrictions on their wide use are considered. There are data on the design of novel representatives of SNRI antidepressants.